2014
DOI: 10.1155/2014/395434
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Computerized Decision Support System to Improve the Appropriateness of Antibiotic Therapy Using Local Microbiologic Data

Abstract: A prospective quasi-experimental study was undertaken in 218 patients with suspicion of nosocomial infection hospitalized in a polyvalent ICU where a new electronic device (GERB) has been designed for antibiotic prescriptions. Two GERB-based applications were developed to provide local resistance maps (LRMs) and preliminary microbiological reports with therapeutic recommendation (PMRTRs). Both applications used the data in the Laboratory Information System of the Microbiology Department to report on the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
“…We found that most work has been conducted in relation to CPOE and CDS systems, focusing on interventions that targeted individual prescribers through prompts and reminders …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations